A system for early budgeting cost of highway maintenance in Malaysia - Abdul Muhaimin Bin Mohd Yunus (School of Environmental Engineering, University Malaysia Perlis, 2014)
This project presents the process of developing an expert system to make an early budgeting for the cost of highway maintenance in Malaysia. Based on interviews with department of public works (PWD) , there are several factors that cause the company fails to get a project or won the tender for highway maintenance work. The main factor is failing to properly estimate the maintenance cost of the highway. In order to properly estimate the cost of the highway, company shall have experience in highway maintenance and know the current rate of work.